China business : the rules of the game - Blackman, Carolyn (St Leonards, N.S.W. : Allen and Unwin, 2000)
The Chinese face of globalisation. Strategic plans meet Chinese reality. Foreign managers, Chinese staff. Bureaucracy and business.
Keywords: Economics; Business; China; International business enterprises; International business enterprises -- China; International business enterprises -- China -- Case studies; Negotiation in business -- China; Negotiation in business -- China -- Case studies; Organizational change -- China; Success in business -- China